ADHM skyrmions. (4th August 2022) - Cork, Josh; Halcrow, Chris
Abstract: We propose, via the Atiyah–Manton approximation, a framework for studying skyrmions on R 3 using Atiyah–Drinfeld–Hitchin–Manin (ADHM) data for Yang–Mills instantons on R 4 . We provide a dictionary between important concepts in the Skyrme model and analogous ideas for ADHM data, and describe an efficient process for obtaining approximate Skyrme fields directly from ADHM data. We show that the approximation successfully describes all known skyrmions with charge B ⩽ 8, with energies reproduced within 2% of the true minimisers. We also develop factorisation methods for studying clusters of instantons and skyrmions, generalising early work by Christ–Stanton–Weinberg, and describe some relatively large families of explicit ADHM data. These tools provide a unified framework for describing coalesced highly-symmetric configurations as well as skyrmion clusters, both of which are needed to study nuclear systems in the Skyrme model.